1995
DOI: 10.1074/jbc.270.42.24745
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the γ Protein and Its Involvement in the Metallocluster Assembly and Maturation of Dinitrogenase from Azotobacter vinelandii

Abstract: Dinitrogenase, the enzyme capable of catalyzing the reduction of N2, is a heterotetramer (␣2␤2) and contains the iron-molybdenum cofactor (FeMo-co) at the active site of the enzyme. Mutant strains unable to synthesize FeMo-co accumulate an apo form of dinitrogenase, which is enzymatically inactive but can be activated in vitro by the addition of purified FeMo-co. Apodinitrogenase from certain mutant strains of Azotobacter vinelandii has a subunit composition of ␣ 2 ␤ 2 ␥ 2 . The ␥ subunit has been implicated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
109
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(113 citation statements)
references
References 30 publications
3
109
0
1
Order By: Relevance
“…This result was not surprising because we had previously shown that a FeMoco-deficient form of the MoFe protein synthesized by a nifH deletion strain could be activated in cell-free extracts on addition of FeMoco, Fe protein, and MgATP but could not be activated by using the same additions once it was purified (22)(23)(24). We also knew from the literature that gamma and possibly other proteins and͞or factors were missing (24,25).…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…This result was not surprising because we had previously shown that a FeMoco-deficient form of the MoFe protein synthesized by a nifH deletion strain could be activated in cell-free extracts on addition of FeMoco, Fe protein, and MgATP but could not be activated by using the same additions once it was purified (22)(23)(24). We also knew from the literature that gamma and possibly other proteins and͞or factors were missing (24,25).…”
Section: Resultsmentioning
confidence: 87%
“…An E146D Fe protein was shown to be fully functional as an electron donor to the MoFe protein and in the initial biosynthesis of FeMoco. This Fe protein variant, however, was partially defective in the final assembly process such that the A. vinelandii strain expressing the E146D Fe protein accumulated both uninserted FeMoco [probably bound to gamma (25)] and a FeMoco-deficient form of the MoFe protein. Analysis of the purified MoFe protein from that strain showed that it was Ϸ55% active because of the fact that only Ϸ55% of its FeMoco sites were occupied (28).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of VNFG and ANFG might be analogous to the function of the ␥ protein in processing nif-encoded apodinitrogenase 1 (dinitrogenase 1 that does not contain FeMo-co) to dinitrogenase 1. The form of apodinitrogenase 1 that is activable by FeMo-co has an ␣ 2 ␤ 2 ␥ 2 composition (25); the ␥ protein, a nonnif-encoded gene product, has been shown to specifically asso-ciate with FeMo-co and perhaps function as a chaperone-insertase in the maturation of apodinitrogenase 1 to dinitrogenase 1 (26).…”
mentioning
confidence: 99%